A Comparative Study on Epidemiology, Spectrum and Outcome Analysis of Physical Trauma cases Presenting to Emergency Department of Dhulikhel Hospital, Kathmandu University Hospital and its Outreach Centers in Rural Area - Shrestha, R; Shrestha, SK; Kayastha, SR; Parajuli, N; Dhoju, D; Shrestha, D (Kathmandu University Medical Journal, 2015)
Background Physical trauma is one of the major cause of mortality and morbidity among young and active age group and its increasing trend is of main concern. There are only few studies concerning the spectrum of physical trauma in Nepal. Objective This study aims to evaluate the epidemiological spectrum, the extent, severity of the physical trauma and the outcome evaluation of patients with physical trauma over a period of one year in the emergency department of the Kathmandu University Hospital and compare the same parameters with those patients presenting to the various outreach centers of the hospital in the community. Methods Patient treatment files from the emergency department and the reports from various outreach centers were retrieved for a period of one year (May 2011 to April 2012). Epidemiological information, mode, type and anatomic location of injuries were recorded. Outcome evaluation was assessed by number of patients discharged from emergency department of the hospital or the outreach centers after the treatment, patients admitted for inpatient management and referred to other centers for further specialty management. Result In a period of one year, total 2205 (20%) of physical trauma cases presented to the emergency department and 1994 (6.12%) in the outreach centres. Most commonly involved age group in physical trauma both in Hospital set up and in Community set up were the young adults (15 to 49 years). Fall from height was the commonest mode of injury followed by road traffic accidents among the patients coming to the hospital while significant number of trauma patients coming to outreach centers were due to fall from height. In the hospital set up, 1525 (69.2%) of the cases were discharged while 537 (24.4%) needed inpatient management and 85 (3.8%) needed referral to other centers for the specialty management. In case of outreaches, half of the patients were discharged after the primary treatment and almost another half were referred to the hospital, mainly for need of further investigations. Conclusion Fall related injuries and road traffic accidents are the most common mode of trauma in the hospital set up and fall related injuries are the single most important mode of trauma seen in the outreaches. Mostly young adults in their active period of life are involved in physical trauma so appropriate preventive measures through public health approach should be included in comprehensive trauma management for reducing mortality and morbidity rates related to physical trauma. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12513 Kathmandu Univ Med J 2013; 43(3):241-246